Standing room only : marketing insights for engaging performing arts audiences - Bernstein, Joanne Scheff, 1945- (Palgrave Macmillan, 2014)
"First published in 1997, Standing Room Only has long been considered the marketing bible for theatre organizations and was the collaborative effort of two professors from Northwestern University's Kellogg School of Business, consistently one of the top-ranked business schools in the nation, Standing Room Only combined practical advice for creating a strategic marketing program and maintaining a successful performing arts organization with innovative examples from real theatre organizations around the nation were harnessing the marketing tools at their disposal to achieving rewarding benefits. Its lessons have been proven to be internationally applicable and easily adaptable to the organization type (theatre, opera, ballet, etc.). In this revised edition, Bernstein will bring the work up to the digital age, cutting the concepts that are no longer as viable in today's market while providing much needed guidance for navigating the possibilities of the internet. From online ticketing options to marketing options in social and mobile media, The new edition provides the framework to effortlessly transition into the online market, along with revealing the innovative ideas other theatres have already successfully integrated into their marketing plans, including the Joffrey Ballet's use of Groupon to expand their outreach and effectively work their pricing strategies to attract a whole new level of patrons. "--